2021
DOI: 10.3389/fimmu.2021.690976
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of Different Emerging Viral Infections: Evasion, Fatal Mechanism, and Prevention

Abstract: Different emerging viral infections may emerge in different regions of the world and pose a global pandemic threat with high fatality. Clarification of the immunopathogenesis of different emerging viral infections can provide a plan for the crisis management and prevention of emerging infections. This perspective article describes how an emerging viral infection evolves from microbial mutation, zoonotic and/or vector-borne transmission that progresses to a fatal infection due to overt viremia, tissue-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 179 publications
(300 reference statements)
0
7
0
Order By: Relevance
“…However, tremendous efforts of the scientists to find out some antiviral therapy, there is no anti dengue drugs in the market presently. It is well known that; beneficial mutations generally map to intrinsically disordered domains of the virus which are clustered to a specific part in the genome [2; 49]. Several studies demonstrated that, the continuous influx of several mutations in the direction of virus adaptation [22; 40].…”
Section: Discussionmentioning
confidence: 99%
“…However, tremendous efforts of the scientists to find out some antiviral therapy, there is no anti dengue drugs in the market presently. It is well known that; beneficial mutations generally map to intrinsically disordered domains of the virus which are clustered to a specific part in the genome [2; 49]. Several studies demonstrated that, the continuous influx of several mutations in the direction of virus adaptation [22; 40].…”
Section: Discussionmentioning
confidence: 99%
“…As such, they are classified as Category A (EBOV), B (WNV), or C (IAV and MERS-CoV) priority pathogens by the NIAID 1 . Host responses against all four viruses are thought to contribute to pathogenesis in severe and fatal cases 2 , 3 . Therefore, the overarching goal of the OMICS-LHV Systems Biology Center was to use global host response data to model virus infections and identify host-dependent mechanisms that regulate severe or fatal disease.…”
Section: Background and Summarymentioning
confidence: 99%
“…Increased liberation of bradykinin, a potent inducer of vascular permeability, has also been reported in hantaviruses infections ( Taylor et al, 2013 ). In addition, the virion glycoprotein (GP) of the Ebola virus has been shown to mediate abnormal activation and disruption of endothelial cells even in the absence of viral replication ( Geisbert et al, 2003 ; Yang and Yang, 2021 ; Moni et al, 2022 ). Humans and nonhuman primates with VHF also present adrenocortical infection and necrosis, leading to impaired secretion of steroid-synthesizing enzymes that cause hypotension and sodium loss due to hypovolemia; these two important events have been reported in nearly all cases of VHF ( Mariappan et al, 2021 ).…”
Section: Clinical Presentation and Pathogenesismentioning
confidence: 99%